2020
DOI: 10.1177/0734371x20973441
|View full text |Cite
|
Sign up to set email alerts
|

Public Service Motivation and Prosocial Rule-Breaking: An International Vignettes Study in Belgium, Germany, and the Netherlands

Abstract: We theorize that people with high Public Service Motivation (PSM) are especially prone to engage in prosocial rule-breaking (PSRB) behavior, which ultimately leads to discriminatory practices, particularly for clients associated with positive affect. We conduct an original vignette study in three countries (Belgium, Germany, and the Netherlands) with 928 observations in total. Our findings provide tentative behavioral evidence on a linear relationship between PSM and the likelihood of PSRB and a strong positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 111 publications
(199 reference statements)
0
31
0
Order By: Relevance
“…For example, Shum et al (2019) found a negative relationship between moral courage and a specific form of PSRB-prosocial rule-breaking behaviors with a motive to help coworkers (i.e., PSBC)-in the hospitality industry. Weißmüller et al (2020) found a positive relationship between public service motivation and PSRB in public-sector employees.…”
Section: Pro-social Rule Breakingmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, Shum et al (2019) found a negative relationship between moral courage and a specific form of PSRB-prosocial rule-breaking behaviors with a motive to help coworkers (i.e., PSBC)-in the hospitality industry. Weißmüller et al (2020) found a positive relationship between public service motivation and PSRB in public-sector employees.…”
Section: Pro-social Rule Breakingmentioning
confidence: 79%
“…In doing so, employees may break out of the organizational boundaries that restrict them from contributing directly or indirectly to the "cause"-going above and beyond to preserve their ideologies. For example, in the public sector, employees with higher public service motivation are more likely to engage in PSRB-namely breaking organizational rules to help the citizens that they believe need and deserve help (Weißmüller et al, 2020). Morrison (2006) identified a few significant predictors of PSRB-autonomy, risk-taking propensity and co-worker behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate pretests of the treatment stimuli were conducted before the experiment was rolled out (Wilson & While, 1998). Prior studies on corruption-related issues using similar (quasi-)experimental study designs and vignette-based framing stimuli found small to medium-sized effects (see, e.g., Weißmüller et al (2020) or Ripoll and Ballart (2020)). In the prospect of small to mediumsized effects (Cohen's d ≤ 0.3; power = 0.8; α = 0.05), samples should comprise at least n = 176 respondents (Ellis, 2010), which has been achieved for each sample.…”
Section: And Ramdani and Vanmentioning
confidence: 99%
“…Adequate pretests of the treatment stimuli were conducted before the experiment was rolled out (Wilson & While, 1998). Prior studies on corruption-related issues using similar (quasi-)experimental study designs and vignette-based framing stimuli found small to medium-sized effects, see, e.g., Weißmüller et al (2020) or Ripoll and Ballart (2020). In the prospect of small to medium-sized effects (Cohen's d ≤ 0.3; power = 0.8; α = 0.05), samples should comprise at least n = 176 respondents (Ellis, 2010), which has been achieved for each sample.…”
Section: Quasi-experimental Research Designmentioning
confidence: 99%